Sally Schneider: The Art of Low-Calorie Cooking - Lucraft, Fiona (Petits Propos Culinaires, 1992)
Sally Schneider: The Art of Low-Calorie Cooking: Stewart, Taboori and Chang, 1990: 256 pp, photography by Maria Robledo, index: £19.95.